In silico approach to ascertain the calcium dependent role of Plasmodium falciparum SERA5. Issue 1 (2nd January 2017) - Rahul, C. N.; Shiva Krishna, K.; Pawar, Atul P.; Rajesh, Vidya
Abstract : The P. falciparum serine repeat antigen (PfSERA5) is the most abundantly expressed protein in the parasitophorous vacuole during the asexual blood stage and serves as both drug and vaccine target. The processed central fragment (56 KDa) of PfSERA5 is implicated to play an important role in parasite exit (egress) during schizont rupture from erythrocytes. Structural characterization of its enzymatic domain supports protease-like function for this central domain. The understanding of exact functional role of PfSERA5 in parasite egress remains unconfirmed as recent studies also indicate an indispensable non-catalytic role for PfSERA5 putative enzyme domain in the blood stage. No structural insight into PfSERA5 prodomain is available. Structure prediction of PfSERA5 prodomain using in silico approach in our study, showed it to have structural similarity with calcium-binding proteins. An earlier observation of steep rise in intracellular calcium concentration as an important factor in egress makes the prodomain calcium-binding role significant. The implication of calcium on structure and activity of PfSERA5 putative enzyme domain is also unknown, and such information would aid to substantiating any calcium-dependent effects on PfSERA5. To understand this, we performed molecular dynamic (MD) simulation both in the presence and absence of calcium. MD results show secondary structure conformational differences in local regions of protein structure. Our results support calcium to be an important parameter for stability and function of PfSERA5. This computational assessment suggest a need to design future experiments like calcium-dependent inhibition studies to reveal exact functional role of PfSERA5 in parasite egress.